2016
DOI: 10.5194/isprs-archives-xli-b4-479-2016
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Planetary Surface Age Based on Crater Statistics Obtained by an Automatic Detection Algorithm

Abstract: ABSTRACT:The analysis of the impact crater size-frequency distribution (CSFD) is a well-established approach to the determination of the age of planetary surfaces. Classically, estimation of the CSFD is achieved by manual crater counting and size determination in spacecraft images, which, however, becomes very time-consuming for large surface areas and/or high image resolution. With increasing availability of high-resolution (nearly) global image mosaics of planetary surfaces, a variety of automated methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…First, Boyce and Johnson [33] suggested that the age of the Tsiolkovsky basalt is 3.8 Ga. As detection data have been continuously updated, Walker et al [6] mapped 4717 impact craters in an area of 7384 km 2 and calculated the basalt age to be 3.8 Ga, i.e., Imbrian. In 1988, Tyrie et al [7] randomly selected 85 basalt regions, excluding those covered by volcanogenic and secondary impacts, and mapped 12604 impact craters with diameters ranging from 70 m to 1 km, deriving a dating result of 3.51 ± 0.1 Ga. Salih et al [8] used Kaguya Terrain Camera images with a resolution of 7.4 m per pixel to select an area of 100 km 2 on the basalt unit at the crater floor as a reference. The selected diameters of the craters ranged from 128 to 1000 m for dating, and the ages were 3.2-3.3 Ga with the youngest being 2.9 Ga and the oldest being 3.6 Ga in local areas.…”
Section: Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…First, Boyce and Johnson [33] suggested that the age of the Tsiolkovsky basalt is 3.8 Ga. As detection data have been continuously updated, Walker et al [6] mapped 4717 impact craters in an area of 7384 km 2 and calculated the basalt age to be 3.8 Ga, i.e., Imbrian. In 1988, Tyrie et al [7] randomly selected 85 basalt regions, excluding those covered by volcanogenic and secondary impacts, and mapped 12604 impact craters with diameters ranging from 70 m to 1 km, deriving a dating result of 3.51 ± 0.1 Ga. Salih et al [8] used Kaguya Terrain Camera images with a resolution of 7.4 m per pixel to select an area of 100 km 2 on the basalt unit at the crater floor as a reference. The selected diameters of the craters ranged from 128 to 1000 m for dating, and the ages were 3.2-3.3 Ga with the youngest being 2.9 Ga and the oldest being 3.6 Ga in local areas.…”
Section: Chronologymentioning
confidence: 99%
“…Later, Walker et al [6] used lunar topographic orthophoto maps to calculate a thickness of 1.75 km and a volume of 3.6 × 10 4 km 3 for basalts in the Tsiolkovsky crater. As lunar exploration datasets are continuously updated, Tyrie et al [7] used Apollo 15 panoramic camera photographs to date the basalt via the crater size-frequency distribution method, and the result was 3.51 ± 0.1 Ga. Later, Salih et al [8] used updated Kaguya Terrain Camera (TC) data to determine that the age of the Tsiolkovsky crater floor is typically 3.2-3.3 Ga. In terms of the mineral distribution, Heather et al [9] used Clementine mosaics to determine that the central peak is feldspathic with very small, locally olivine-rich outcrops.…”
Section: Introductionmentioning
confidence: 99%